1989
DOI: 10.1001/archotol.1989.01860310055022
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Adenosine Triphosphatase Activity in the Absence of Adrenocorticosteroids

Abstract: \s=b\ Changes in adenosine triphosphatase activity and cellular integrity of rat innerear tissues were observed after removal of adrenal steroids via bilateral adrenalectomy. Statistical significance of total and magnesium ion-dependent adenosine triphosphatase activities of the stria vascularis, spiral ligament, and ampullar dark cells from adrenalectomized animals was detected when compared with those of controls as demonstrated by fluorometric microassay. Although there was a similar reduction of activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…et al, 1998). Studies in rat have shown a positive correlation between serum levels of corticosteroid (glucocorticoid and mineralocorticoid) hormones and the amount of Na + ,K + -ATPase in the inner ear Rarey et al, 1989). Low levels of GRs in immunostaining and ELISA were observed in the previously studies in the SV (Rarey and Curtis, 1996;Zuo et al, 1995).…”
Section: Discussionmentioning
confidence: 80%
“…et al, 1998). Studies in rat have shown a positive correlation between serum levels of corticosteroid (glucocorticoid and mineralocorticoid) hormones and the amount of Na + ,K + -ATPase in the inner ear Rarey et al, 1989). Low levels of GRs in immunostaining and ELISA were observed in the previously studies in the SV (Rarey and Curtis, 1996;Zuo et al, 1995).…”
Section: Discussionmentioning
confidence: 80%
“…In recent experiments, a relationship between circulating adrenal steroids and Na/K-ATPase activity in the inner ear was observed [10,11]. Emotional stress leads to the activation of neuroendocrine effector systems, including the production of adrenal steroids such as aldosterone, and could thus increase the production of endolymph.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine triphosphatase activity was decreased in the stria vascularis, spiral ligament and ampullar dark cells, but not in utricular dark-cell tissues in adrenalectomized rats [141].…”
Section: Changes Due To Altered Levels Of Endogenous Corticosteroidsmentioning
confidence: 79%
“…The morphological integrity of the cellular architecture of the stria vascularis [141][142][143] and the ampullar dark cells [141,144,145] is dependent on an adequate plasma corticosteroid level in rats. When diet-induced mineralocorticoid deficiency is substituted with aldosterone, the number of Na + ,K( + )-ATPase sites in the lateral cochlear wall and in the ampullae of the semicircular canal is increased in guinea pigs [85].…”
Section: Changes Due To Altered Levels Of Endogenous Corticosteroidsmentioning
confidence: 99%